Alfabetização e letramento digital na formação docente para os anos iniciais do ensino fundamental - Landin, Rita de Cassia de Souza (2021)
In the midst of digital information and communication technologies, it is not enough for the teacher to know how to use these technologies on a daily basis. The society of the technological age brings the need for teaching knowledge about digital information and communication technologies in order to pedagogically incorporate them into educational practices. In this doctoral research entitled 'Literacy and digital literacy in teacher education for the early years of elementary school', we aim to analyze how literacy and digital literacy in teachers was incorporated into initial teacher education courses for the early years of elementary school, specifically of the Licentiate Degree courses in Pedagogy, from Resolution CNE/CP nº 1 of February 18, 2002, the National Curriculum Guidelines for the Graduate Course in Pedagogy of 2006, Resolution nº 2 of July 1, 2015. For this purpose, we investigated the training proposals of fifteen higher education institutions in Brazil, with grade 5 in ENADE/2017 and that made their Political Course Projects available online or for download in PDF. From the reading of these documents, and specifically the syllabuses of disciplines that address TDICs, we analyze the nature of such disciplines and how they address disciplinary and professional knowledge about TDICs and the pedagogical area, as well as the concepts of technology and literacy and teaching digital literacy that subsidize the years of initial training. In the fifteen institutions analyzed, we found thirty-four subjects that propose the study of TIDCs, and in more than 70% of the HEIs these subjects are mandatory, the prevailing technology concept is that of information and communication technology, and there is the proposal training from the perspective of literacy and teacher digital literacy. However, despite these data, which we analyzed as positive, we observed the absence of curricular integration between disciplinary knowledge about TDICs and disciplinary knowledge in areas related to pedagogical knowledge, specifically those focused on the early years of elementary school. Our main theoretical contributions in the area of technology and teacher education were Vani Moreira Kenski, Maria Luiza Belloni, Monica Fantin and Pier Cesare Rivoltella; in teacher education Bernadete Angelina Gatti, Elba Siqueira de Sá Barreto and Marli Eliza Dalmazo de Afonso André, as well as training documents from the Ministry of Education, and in literacy and digital literacy Monica Fantin and Pier Cesare Rivoltella, Monica Fantin and Gilka Elvira Ponzi Girardello , Carolyn Wilson, Alton Grizzle, Ramon Tuazon, Kwame Akyempong and Chi-Kim Cheung and Marisa Narciso Sampaio and Lígia Silva Leite.